PENGEMBANGAN E-MODUL BERBASIS PEMBERDAYAAN BERPIKIR MELALUI PERTANYAAN (PBMP) UNTUK SISWA SMA PADA MATERI SISTEM IMUN - Wulandari, Hartati; Zulfarina, Zulfarina; Suryawati, Evi (Universitas Lancang Kuning, 2024)
Based on the results of observations that have been carried out in several high schools in Pekanbaru, it can be concluded that it is very necessary to develop teaching materials in the form of E-modules because teachers only use textbooks and LKPD during the teaching and learning process, teachers have never used E-modules during learning. And teachers do not use learning resources that can support students' critical thinking skills. Students experience difficulty in providing arguments when asked for written explanations to solve problems, and students are unable to analyze and synthesize problems. The aim of this study was to determine the effectiveness and efficiency of the electronic components of the immune system of PBMP. It is hoped that this study can help teachers to choose new learning materials as an alternative to support learning during the 4.0 revolution, and to provide learning experiences using electronic components. PBMP (problem-based empowerment) and encourage learning. Students will study the resources of the immune system so that students can think critically to develop. The efficiency test results are classified as very efficient which can be seen in the average relevance of 96.08% in the most effective category.